2016
DOI: 10.4103/2229-5151.183025
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury related research in India: An overview of published literature

Abstract: Aim:This paper provides an overview of publications by Indian researchers on traumatic brain injury between 1966 and 2014, to set up a platform for evaluating and synthesizing the results and findings from brain injury research in India.Materials and Methods:All published articles from India related to brain injury since 1966 to 2014 were retrieved from PubMed using the search for (“craniocerebral trauma”[MeSH Terms] OR (“craniocerebral”[All Fields] AND “trauma”[All Fields]) OR “craniocerebral trauma”[All Fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 3 publications
0
32
0
Order By: Relevance
“…The long-term survival after injury is often ignored in the studies on outcome of severe TBI from India. 3 In our study of validation of outcome measure, comprising 88 patients with severe TBI, we found that the inhospital mortality was 20.3% which increased to 30.4% at 6 months. We also found that the disability rating scale (DRS) at the time of discharge had good correlation with outcome at 6 months.…”
mentioning
confidence: 73%
“…The long-term survival after injury is often ignored in the studies on outcome of severe TBI from India. 3 In our study of validation of outcome measure, comprising 88 patients with severe TBI, we found that the inhospital mortality was 20.3% which increased to 30.4% at 6 months. We also found that the disability rating scale (DRS) at the time of discharge had good correlation with outcome at 6 months.…”
mentioning
confidence: 73%
“…43 An interprofessional research team approach involving TBI patients and their caregivers can help us conduct translational research, from reduction of risk factors to optimizing outcomes. 44,45…”
Section: Future Researchmentioning
confidence: 99%
“…Thus, a trauma registry will provide a comprehensive instrument to process data and analyze the epidemiological and research gap between developed countries and India. [1][2][3][4][5] Globally, trauma registries have become important sources of data for TBI research. Yet, a dedicated TBI registry is able to delineate more precise evidence on effective interventions to clearly demark timelines for implementation, monitoring, and evaluation, and scale up futuristic plans.…”
Section: Traumatic Brain Injury Registry: Need Of the Hourmentioning
confidence: 99%